Efektivitas Terapi Guided Imagery untuk Mengurangi Nyeri Akut pada Pasien Pasca Operasi dengan Carcinoma Mammae Sinistra: Studi Kasus - Fitria Awaliyah; Rosiana Nur Imallah (Journal of Health, Medical, and Psychological Studies, 2026)
Acute postoperative pain in patients with left breast carcinoma is a clinical problem that requires a comprehensive approach. This study aimed to evaluate the effectiveness of guided imagery therapy in reducing pain intensity in post-mastectomy patients. The method used was an empirical descriptive case study of a 50-year-old female patient undergoing treatment in the surgical ward of a referral hospital. Guided imagery interventions were administered for 10–15 minutes per session, once daily for three days, and conducted two hours after ketorolac administration. Data were collected through observation, interviews, and medical record documentation using the NRS scale, PQRST, and vital sign monitoring. Results showed a decrease in pain scores from 7 to 3, accompanied by improvements in blood pressure and pulse rate. The effectiveness of the therapy was influenced by the combination of pharmacological and non-pharmacological interventions. Guided imagery played a role in enhancing relaxation and reducing the patients’ stress response. However, the limitations of the case study design restrict the generalizability of the results. Further research is needed for additional validation.